Relationship between the Village Head and the Village Consultative Body in Handling Covid-19 in Ubung Village - Belinda Sam; Darwin Abd Radjak; M Chairul Basrun Umanailo; Andries Lionardo; Bagus Irawan (Jurnal Administrasi Publik (Public Administration Journal), 2021)
The purpose of this study is to establish a relationship between the village head and the village consultative body in Ubung, Buru Regency. The research problem is focused on the collaboration between the village head and the village consultative body in containing the spread of Covid-19 in Ubung. The study employed a qualitative approach, with a total of twenty informants chosen at random. This study was conducted in the village of Ubung, with informants including village officials, members of the Village Consultative Body, representatives of community leaders, traditional leaders, and religious leaders, as well as community representatives considered to possess competencies relevant to the research objectives. This study collects data about the partnership relationship through observation and in-depth interviews. The analysis technique used is qualitative data analysis under Miles, Huberman, and Spradley's concepts. This study concludes that the village is extremely responsive in planning and implementing the management of Covid-19, making it easier for the community to be involved. The village side also adjusts to the existing conditions to carry out the control of Covid-19, specifically by conducting analysis and identification to decipher the program of activities that will be planned in collaboration with the Village Consultative Body. In the division of Village Consultative Body tasks, the village government prioritizes development sector implementation and public awareness, while the village government focuses more on-field segmentation planning.